Propriedades eletrônicas e estruturais de nanotubos de dióxido de titânio por primeiros princípios - Andre Alves Lino (2007)
In this work, we perform first-principles calculations based on the Density Functional Theory (DFT) to study structural and electronic properties of TiO2 nanotubes. Firstly, we address structural aspects. For this purpose we consider a model in which the nanotubes are obtained by rolling up layers of anatase TiO2 oriented in the (001) direction. Thestability of the resulting structures are investigated by comparing the strain energy of the nanotubes with the surface energies of TiO2 nanoribbons. The results show that nanotubes become energetically competitive for diameters around 70 °A, in excellent agreement whit the diameter distribution of observed TiO2 nanotubes. Next, we considerelectronic properties, aiming at the possibility of gap modulation by the application of transverse electric fields. In fact, we show that a giant Stark effect takes place, which is responsible for a significant gap reduction. Moreover, we study the effect of nitrogen and carbon doping on the electronic structure of TiO2 layers (similar results are expected fornanotubes). These dopings may be useful in the attempt to bring the threshold of optical absortion of TiO2 compounds from the ultraviolet to the visible region of spectrum.